The Development of Coastal and Marine - Widjojo, Suharto; Suharjo, Suharjo (Universitas Muhammadiyah Surakarta, 1999)
Planning and development process of oastaland marine resources tends centralized and adopted top down policy, without any active participations from coastal and marine communities. In order to reach integrated and sustainable development in coastaland marine areas, people should have both complete and up to date information, so that planning and decision making for all aspect of the environment can be done easily. People should give a high attention of surveis, mappings, as well as science and technology of coastal and marine sectors, in order to change the paradigm of development from inland to coastal and marine. Moreover, people should give high attention of potential resources of coastal and marine areas.